2008
DOI: 10.1016/j.str.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of the Pre-mRNA Splicing Machine

Abstract: Most eukaryotic pre-mRNAs contain non-coding sequences (introns) that must be removed in order to accurately place the coding sequences (exons) in the correct reading frame. This critical regulatory pre-mRNA splicing event is fundamental in development and cancer. It occurs within a mega-Dalton multicomponent machine composed of RNA and proteins, which undergoes dynamic changes in RNA-RNA, RNA-protein, and protein-protein interactions during the splicing reaction. Recent years have seen progress in functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
107
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 86 publications
(160 reference statements)
3
107
0
2
Order By: Relevance
“…In addition, multiple shorter fragments were present in the gradients, with apparent lengths of 22, 30, and 50 nt that reflected some of the fragments observed in the RNA-seq experiments. Some of these RNAs are present in fractions 8-11 that contain most of the in vivo spliceosomes (37,48) as determined by the presence of five spliceosomal U small nuclear ribonucleoproteins (snRNPs) (Fig. S1D) and regulatory splicing factors (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, multiple shorter fragments were present in the gradients, with apparent lengths of 22, 30, and 50 nt that reflected some of the fragments observed in the RNA-seq experiments. Some of these RNAs are present in fractions 8-11 that contain most of the in vivo spliceosomes (37,48) as determined by the presence of five spliceosomal U small nuclear ribonucleoproteins (snRNPs) (Fig. S1D) and regulatory splicing factors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gradient was subdivided into four parts: A-D. Fraction A contained proteins that sedimented faster than 200S and was devoid of spliceosomes; fraction B contained supraspliceosomes that sedimented in the 200S region (37,48,49), fraction C contained native spliceosomes that sedimented at 60-70S (37,41,50), and fraction D contained proteins and small RNAs that appeared as free proteins or assembled into small RNP complexes. SNORD2, SNORD60, and SNORD78 were present in fractions B and C associated with spliceosomes but devoid of fibrillarin (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…1 This process constitutes the removal of non-coding sequences (introns) from pre-mRNAs and subsequent ligation of the coding sequences (exons) to form a mature mRNA. [2][3][4] Several cis (pre-mRNA) and trans (snRNPs, accessory proteins) acting elements coordinate this process with high precision, to ensure fidelity. Higher eukaryotes contain a U2-dependent (major) splicing pathway and a less abundant U12-dependent (minor) pathway, which splices specific premRNA introns (U2-type and U12-type) differing in the splice site and branch point consensus sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The U2-dependent pathway involves U1, U2, U5 and U4/U6 snRNPs while the U12-dependent pathway comprises of U11, U12, U5 and U4atac/U6atac snRNPs. 5 Multiple intermediary complexes (E, A, B, B act , B Ã and C) which are characterized by synergistic protein-protein, protein-RNA and RNA-RNA interactions 2,3 are involved in these pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentation and co-fractionation experiments in, for example, maize have demonstrated that these proteins are part of large multiprotein and ribonucleoprotein complexes with their cognate RNAs (5,7). In addition, these complexes resemble the nuclear spliceosome in which the snRNAs associate with more than 200 proteins (8).…”
mentioning
confidence: 99%